CELEBRITY PHILANTHROPY: KEDERMAWANAN MUSLIM KELAS MENENGAH DI INDONESIA - Lyansari, Kirana Nur (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Abstract: This article describes the phenomenon of celebrities involvement in Islamic philanthropy in Indonesia. The author focuses on Peggy Melati Sukma, a celebrity figure who had hijrah (spiritual transformation). She was actor, host and model. However, after hijrah, she was committed to focus on managing Islamic philanthropic. The data of this article are collected from Peggy Melati Sukma’s autobiography books, social media observations (netnography) and joined Peggy Melati Sukma's taklim offline. To analyze this phenomenon, the author uses qualitative research with narrative analysis method. This article finds that celebrity philanthropy tends to take advantage of the Islamic market momentum, combined of piety, happiness and satisfaction, as well as fashion. In contrast to other philanthropic institutions that utilize cultural capital, celebrity philanthropy emphasizes the celebrity popularity or their images to gain the trust of the public. Furthermore, celebrity philanthropy is an alternative choice among the other philanthropic institutions. This research contributes to the Islamic philanthropy discussion in Indonesia, specifically celebrity involvement.Keywords: Covid-19; Philanthropy; Islamic Market; Piety; Celebrity.Abstrak: Artikel ini mendiskripsikan fenomena keterlibatan selebriti dalam kegiatan filantropi Islam di Indonesia. Penulis fokus melihat satu figur selebriti hijrah yaitu Peggy Melati Sukma. Dia sebelumnya berprofesi sebagai pemain sinetron, pembawa acara juga model. Namun setelah hijrah, ia berkomitmen untuk fokus mengelola kegiatan filantropi Islam. Data di artikel ini dikumpulkan dari buku-buku autobiografi, observasi media sosial (netnografi) dan mengikuti taklim Peggy Melati Sukma secara offline. Untuk menganalisis fenomena ini, penulis menggunakan penelitian kualitatif dengan metode analisis naratif. Artikel ini menemukan bahwa filantropi selebriti cenderung memanfaatkan momentum pasar Islam, bentuk kombinasi antara kesalehan, kebahagiaan dan kepuasan, juga fesyen. Berbeda dengan lembaga filantropi lainnya yang memanfaatkan modal kultural, filantropi selebriti lebih menonjolkan kepopuleran figure atau image selebriti untuk mendapat kepercayaan dari masyarakat. Selain itu, keberadaan filantropi selebrity menjadi pilihan alternatif di antara lembaga filantropi lainnya. Penelitian ini berkontribusi menambah diskusi tentang filantropi Islam di Indonesia, secara khusus mengenai keterlibatan selebriti.Kata Kunci: Covid-19; Filantropi; Pasar Islam; Kesalehan; Selebriti.